Prevalensi Malaria Klinis dan Positif Plasmodium spp. Berdasarkan Mass Blood Survey di Kabupaten Rokan Hilir Provinsi Riau - Zaenal Abidin; Andri Dwi Hernawan (ASPIRATOR - Journal of Vector-borne Disease Studies, 2010)
Based on clinical diagnosis, the regency of Rokan Hilir in Riau Province is a high malaria endemic areas with annual parasite incidence more than 50 per 1,000 inhabitants, and every year the number of cases continues to rise. To overcome this, the intensification of eradication activities has been conducted with the goal of reducing malaria transmissionrates, cases and deaths due to malaria. To determine the prevalence of positive malaria Plasmodium, in Rokan Hilir regency, has conducted mass blood survey (MBS) in March 2008 in 5 villages which is the highest malaria endemic areas. The number of people who checked his blood sample was 5215 people (18,42% of the total population), 1252 of whom were residents age group 0-9 years.From the examination results are known 267 people (5.12%) positive malaria, including 86 people in the population age group 0-9 years.Furthermore, the survey concluded that the location of high malaria endemic area for 5.12% of samples tested positive for malaria and malaria morbidity in the population age group 0-9 years is 6.87%.